2017
DOI: 10.3329/jbcps.v35i2.33366
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bronchial Brush Cytology in Diagnosis of Central Bronchial Carcinoma

Abstract: Background : Despite the advances in imaging techniques and treatment modalities, the prognosis of lung cancer remains poor, with five-year survival of 14% at early stages and less than 5% in locally advanced stages. Before starting treatment a clear distinction between small cell and nonsmall cell carcinoma must be made, for that histopathology remains the mainstay of confirmation of diagnosis. To combat the disease successfully, it should be diagnosed at earliest possible stage. If bronchial brush cytology y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Sultana B et al showed squamous cell carcinoma 48.6%, adenocarcinoma 10.8 %, small cell carcinoma 08%, and no malignancy in 32.4% of cases. 21 The frequency of squamous cell carcinoma is similar to the study by Sultana B et al 21 , but it differs from other types.…”
Section: Discussionsupporting
confidence: 81%
“…Sultana B et al showed squamous cell carcinoma 48.6%, adenocarcinoma 10.8 %, small cell carcinoma 08%, and no malignancy in 32.4% of cases. 21 The frequency of squamous cell carcinoma is similar to the study by Sultana B et al 21 , but it differs from other types.…”
Section: Discussionsupporting
confidence: 81%
“…The age distribution was comparable to the studies done by Behura et al .,[ 4 ] B Sultana et al . [ 12 ], Giti et al .,[ 13 ] and Sareen et al . [ 14 ] The male-to-female ratio in this study was 2.7:1 that was comparable with the study done by Choudhury et al .…”
Section: Discussionmentioning
confidence: 99%